INFLUENCE OF USE OF FIGURE TOOL FROM USED MATERIALS TOWARDS STUDENT LEARNING RESULTS IN SMP NEGERI 1 KUPANG CITY ACADEMIC YEAR 2018/2019 - Riwu Lobo, Ance Sayani (Prodi Pendidikan Biologi FKIP Universitas Kristen Artha Wacana, 2022)
The purpose of this study was to determine the effect of the use of teaching aids from used materials on student learning outcomes. The population of all students in class VIII was 198 students and sample of class VIIIB and class VIIIC totaled 61 students. The method used is an experimental method with the Posstest-Only Control Group Design. The sampling technique used is Cluster Sampling. Data collection is done by learning achievement tests. Student learning outcomes data obtained were analyzed using the t test, with the help of SPSS. Based on the homogeneity test results obtained an F value of 6,560 and the hypothesis test results obtained t value of 11,403 with a significance of 0,000 or less than 0.5 it shows that there are differences in student learning outcomes between the control class and experiment. because by using props students can see directly. This can be seen from the average value of 85.81 compared to student learning outcomes in the control class. Because in the experimental class students more actively find out for themselves about important concepts in learning so that students more easily remember, understand, apply and apply what is found in learning. Thus it can be concluded that H1 is accepted and H0 is rejected, meaning that there is a significant influence in the use of teaching aids on student learning outcomes.